Identification of the novel HLA‐B*18:37:02 allele in a Croatian individual. (14th March 2018) - Burek Kamenaric, M.; Maskalan, M.; Drabbels, J.; Golubic Cepulic, B.; Grubic, Z.
Abstract : The new allele HLA‐B*18:37:02 differs from HLA‐B*18:37:01 by one nucleotide substitutions in exon 2.